Peran Sekolah dalam Pendidikan Migitasi Bencana - Idha Lusmianingtyas; Suwarno Suwarno (UM Purwokerto Press, 2022)
Indonesia is an archipelagic country and between the plates of the earth. Geographically, Indonesia is one of the countries prone to natural disasters such as landslides, earthquakes, tsunamis, floods, volcanic eruptions and other events. Natural phenomena come uninvited and appear suddenly which create panic and pressure for humans. Natural disasters are very dangerous for human safety, both property and life. Besides that, natural disasters leave various damages in the ecosystem of living things that will affect human life. Natural damage will have a significant effect on human life during the Encana, disaster management and during the recovery period. One solution to minimize disaster risk, schools can play a role by means of disaster mitigation education in order to build students' understanding and skills in disaster mitigation education in the school and community environment. This article was written using qualitative research methods. The research process by interacting directly through observation, recording, and digging up sources of information related to the events under study as well as reviewing library references from books, journals and scientific papers on disaster mitigation. Next, the author analyzes ideas with relevant theories regarding the role of schools in disaster mitigation education. The government together with education units or schools must integrate disaster mitigation materials in the curriculum as one of the right solutions to improve the competence of students in dealing with disasters and disaster mitigation. Strategic efforts that can be taken include disaster mitigation literacy programs, integrating disaster mitigation materials in subjects and extracurricular activities.